Effect of Antiepileptic drugs on lipid profile in children with Epilepsy - Jayashree Nadkarni; Deepak Kumar Uikey; Utkarsh Sharma; Rashmi Dwivedi (International Journal of Medical Research and Review, 2014)
Objective: The study evaluated the effect of antiepileptic drugs on lipid profile in children with epilepsy. Demographic profile and the seizure pattern of CWE were also studied.Material and method: 95 children aged between 2-15 years with confirmed diagnosis of primary epilepsy who were on AED for at least 3 months were the cases and 50 normal healthy children of similar age group were the controls. Children with BMI >95th entile were excluded. The cases were categorized in three groups depending upon whether they were taking either phenytoin, valproic acid alone or in combination.Result: The Levene‘s test for homogeneity of variance indicated a significant difference in variance between the cases and control group in serum TGs, LDL-C and VLDL-C. The t-test showed a significant difference in means among cases and controls in HDL-C, LDL-C levels and the risk ratio.Conclusion: We recommend a need for careful monitoring of lipid profile in children with epilepsy receiving antiepileptic drugs